Strategi Kepala Sekolah dalam Mengatasi Tantangan SDM di Sekolah Islam Swasta di Kabupaten Balangan - Miranti Miranti (STIT Syekh Muhammad Nafis Tabalong, 2025)
This research is motivated by the complex challenges of human resource management in private Islamic schools in Balangan Regency, particularly related to teacher competency development, work motivation, and limited funding. The focus of this research is the strategies implemented by school principals in overcoming these various challenges to improve the quality of human resources in the school environment. The purpose of this research is to identify and analyze the leadership strategies of school principals in managing human resources in several private Islamic schools, including SMAS Al-Hidayah Inan, MIS Nurul Irsyad, MIS Bustanul Ulum, SD IT Al Falah, and PAUD IT Al-Busyra. The research method used is a qualitative case study approach. Data were collected through in-depth interviews, observations, and supporting documentation, then analyzed descriptively qualitatively. The results show that school principals implement various adaptive strategies, such as internal training and mentoring for teacher competency development, providing non-financial rewards and spiritual guidance to increase motivation, and establishing partnerships with external institutions to overcome limited funding. Strengthening Islamic values ​​is also an important part of human resource leadership in these schools. In conclusion, adaptive, collaborative leadership based on Islamic values ​​is key to addressing human resource challenges and improving the quality of education in private Islamic schools in Balangan Regency.